FINANCIAL TECHNOLOGY INNOVATION AND BANKING INDUSTRY TRANSFORMATION: A LITERATURE STUDY ON FINANCIAL MARKETS - Bakri, Asri Ady; Hasanah, Niswatun; Lasmiatun , KMT (Multifinance, 2024)
This research aims to innovate in technology, finance, and transformation in the banking industry. The research method used in this research is qualitative. Qualitative research is a research method used to understand social phenomena in depth. This type of research is library research, which researchers carry out by collecting, studying, and analyzing references or sources. obtained in writing or written form, such as books, journals, articles, documents, and other sources of information that are significant to the topic or title being researched. The research results show that the impact of development technology on industry banking in Indonesia is positive, namely: Improvement Efficiency and Productivity: Adoption technology has brought significant enhancements to efficiency bank operations, with automation of processes and usage intelligence artificial to reduce costs and improve productivity. Enhancement Experience Customer: Innovation technology has allowed banks to increase customer experience through applications in digital banking, customer chatbot-based services, and self-service platforms. Enhancement Security and Management Risk: Although there are worries related to data security, development technology has the potential to repair significant system security and management risks. With the use of data encryption and analysis behavior, users can identify and respond to threats to security more quickly. Innovation Products and Services: Technology has pushed the development of new products and services in the banking industry, including robo-advisors, peer-to-peer lending platforms, and applications for mobile payments, which deliver a markup for customers and help banks expand their market share. Enhancement Efficiency and Transparency Management: System Management Integrated information and analytical dashboards have increased efficiency and transparency in bank management.